2021
DOI: 10.3390/s21248348
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sensitivity and Profitability of an Intravaginal Sensor for Remote Calving Prediction in Dairy Cattle

Abstract: One critical point of dairy farm management is calving and neonatal first care. Timely calving assistance is associated with the reduction of calf mortality and postpartum uterine disease, and with improved fertility in dairy cattle. This study aimed to evaluate the performance and profitability of an intravaginal sensor for the prediction of stage II of labor in dairy farms, thus allowing proper calving assistance. Seventy-three late-gestating Italian Holstein cows were submitted to the insertion of an intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…In this study, 32% of deliveries occurred during the night hours, that is, from 18:00 to 04:59. The prevalence of night-occurring calving was similar to the distribution observed in a previous study [17], while other investigations have either reported an opposite trend, especially in primiparous animals [9], or an equal distribution [18]. Herein, parity was not associated with day-or night-occurring calving.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, 32% of deliveries occurred during the night hours, that is, from 18:00 to 04:59. The prevalence of night-occurring calving was similar to the distribution observed in a previous study [17], while other investigations have either reported an opposite trend, especially in primiparous animals [9], or an equal distribution [18]. Herein, parity was not associated with day-or night-occurring calving.…”
Section: Discussionsupporting
confidence: 87%
“…Cow behavior was unaltered by the presence of the device in the vaginal cavity, as determined by a detailed cow behavior scoring system including observations of eight possible signs of discomfort and pain. Although the e-Synch device has a different shape and dimensions than other electronic IVG devices for cattle, our observations agree with the lack of changes in cow behavior or pain observed after insertion of IVG devices (Crociati et al, 2021;Stephen and Norman, 2021). The tail raising scores dynamic for cows that received an i.m.…”
Section: Discussionsupporting
confidence: 78%
“…The remote system has been evaluated for use both in cattle [57] and buffaloes [58]. Field trials demonstrated an overall Se = 86.3% [60], a good local tolerance and a high retention rate, except in one case of recurrent vaginal prolapse in a buffalo heifer.…”
Section: Intravaginal Devicesmentioning
confidence: 99%